Acute Viral Hepatitis A and B: A Four Year Retrospective Analysis - Elaldı, Nazif; Türkoğlu, Nurcan; Erandaç, Memnune; Dökmetaş, İlyas; Bakır, Mehmet (Fırat University, 2002)
Background: Acute viral hepatitis (AVH), caused by a number of viral agents and characterised by hepatic inflammation and injury, is an infectious disease. AVHs, mainly acute viral hepatitis B (AVHB) cause important morbidity and mortality around the world. Material and Method: Hospitalised patients with acute viral hepatitis A (AVHA) and AVHB at the Department of Clinical Bacteriology and Infectious Diseases. Cumhuriyet University Hospital, Sivas, between January 1996 and December 1999 were analysed retrospectively. Results: During the four-year study period, 41 (35%) female and 75 (65%) male totally 116 patients were diagnosed as AVH and hospitalised at our clinic. Forty-three (37%) of them were AVHA and 73 (63%) AVHB. Mean age was 19 (yr) for AVHA cases and 32 (vr) for AVHB (p< 0.05). The patients with AVHB had a longer hospitalisation period than the patients with AVHA (9 r.v 12 days, p< 0.05). Conclusion: Our study shows that, AVHA has seen in young patients more than AVHB, and the patients with AVHB have a longer hospitalisation period at the clinic than the patients with AVHA.

Giriş: Akut viral hepatit (AVH)'ler, birçok viral ajanın etken olduğu, karaciğerde inflamasyon ve nekrozla karakterize bir infeksiyon hastalık ve başta Akut Viral Hepatit B (AVHB) olmak üzere tüm dünyada önemli morbidite ve mortalite nedenidir. Gereç ve Yöntem: Sivas Cumhuriyet Üniversitesi, Tıp Fakültesi Hastanesi, infeksiyon Hastalıkları ve Klinik Bakteriyoloji Bilim Dalı'nda Ocak 1996 ile Aralık 1999 arasında Akut Viral Hepatit A (AVHA) ve AVHB tanılarıyla takip edilen hastalar geriye yönelik olarak incelendi. Bulgular: Kliniğimize dört yıllık takip süresi içinde 41 (%35) kadın. 75 (%65) erkek toplam 116 hasta AVH nedeniyle yatırılarak takip edildi. Hastaların 43 (%37)'ü AVHA, 73 (%63)'ü ise AVHB idi. AVHA'li hastalanıl yaş ortalaması 19 (yıl), AVHB'li hastaların yaş ortalaması ise 32 (yıl) idi (p< 0.05). AVHB'li hastalar AVHA'lı hastalara göre kliniğimizde daha fazla süreyle yatırılarak takip edildiler (9'a karşı 12 gün. p< 0.05). Sonuç: Çalışmamız, AVHA'nın, AVHB'ye göre genç yaştaki hastalarda görüldüğünü ve AVHB'li hastaların AVHA'li hastalara göre klinikte daha fazla süreyle yatırılarak takip edildiğini göstermektedir.
AKUT VİRAL HEPATİT A VE B: DÖRT YILLIK RETROSPEKTİF ÇALIŞMA